Sedimentologika: a community-driven diamond open access journal in sedimentology - Camille Thomas; Aurelia M-L. J. Privat; Romain Vaucher; Yvonne Spychala; Valentin Zuchuat; Marta Marchegiano; Miquel Poyatos-Moré; Ian Kane; Domenico Chiarella (Sedimentologika)
Sedimentologika is a community-driven Diamond Open Access scientific journal for the publication of work in the broad area of sedimentology and stratigraphy. The journal aims to provide a platform to the academic community and broader society, offering and guaranteeing permanent free publication and free access to peer-reviewed scientific studies focusing on all types of sedimentary processes, deposits, and environments across all spatial and temporal scales, on Earth or any other planetary body. It will publish high-quality research that will advance the field of sedimentary science, and will encourage multidisciplinarity, new teaching practices, tools and methods, and progress in accessibility to science. Sedimentologika is part of an ongoing broader Diamond Open Access movement in geosciences aspiring freedom from the financial barriers and pressures of private publishing houses, to provide direct and equal access to science for all citizens, scientists, and institutions worldwide. The published material will include research, review, methodology and opinion articles, which will be free to share, as the authors will retain the copyright of all the submitted material. Manuscripts will be published in English. Authors can attach a second abstract in a language of their choice, further allowing local communities, students, or decisional bodies to access, at least, a summary of the latest research, thus reducing potential language barriers. Sedimentologika follows Open Science principles to promote ethical dissemination and accessibility of science and knowledge, following high equity, diversity and inclusion standards. Sedimentologika emerged as a solution for the scientific community to sidestep structural inequality of the academic publishing system that is becoming financially unsustainable to its payers (authors, funding agencies), and to commit to bibliodiversity. The objective is to ensure that scientific findings remain accessible to all in order to keep advancing research and informing society on how we understand sedimentology and stratigraphy in the world around us. Sedimentologika is driven by the academic and scientific community for the community and society, promoting self-governance and adapting to the needs expressed by the community.